Overview of the Most Promising Radionuclides for Targeted Alpha Therapy: The "Hopeful Eight" - Romain Eychenne; Michel Chérel; Férid Haddad; François Guérard; Jean-François Gestin (MDPI AG, 2021)
Among all existing radionuclides, only a few are of interest for therapeutic applications and more specifically for targeted alpha therapy (TAT). From this selection, actinium-225, astatine-211, bismuth-212, bismuth-213, lead-212, radium-223, terbium-149 and thorium-227 are considered as the most suitable. Despite common general features, they all have their own physical characteristics that make them singular and so promising for TAT. These radionuclides were largely studied over the last two decades, leading to a better knowledge of their production process and chemical behavior, allowing for an increasing number of biological evaluations. The aim of this review is to summarize the main properties of these eight chosen radionuclides. An overview from their availability to the resulting clinical studies, by way of chemical design and preclinical studies is discussed.